2022
DOI: 10.3389/fncel.2022.1049562
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis potential of oligodendrocyte precursor cells from oligospheres and injured spinal cord

Abstract: Severe traumatic spinal cord injury (SCI) leads to long-lasting oligodendrocyte death and extensive demyelination in the lesion area. Oligodendrocyte progenitor cells (OPCs) are the reservoir of new mature oligodendrocytes during damaged myelin regeneration, which also have latent potential for neurogenic regeneration and oligospheres formation. Whether oligospheres derived OPCs can differentiate into neurons and the neurogenesis potential of OPCs after SCI remains unclear. In this study, primary OPCs cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…B6.Cg-Gt(ROSA) 26Sor tm9(CAG−tdTomato)Hze / J female mice (n = 3), 8-week-old wild-type female mice (sham group, n = 9; SCI group, n = 9), 1-week-old (sham group, n = 6; SCI group, n = 6) and 2-week-old juvenile mice (sham group, n = 6; SCI group, n = 6), were used for spinal cord crush model construction. Contusion and crush models at T10 were established as we previously reported (Zhao et al, 2022). The sham-treated mice received laminectomy without contusion and crush.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…B6.Cg-Gt(ROSA) 26Sor tm9(CAG−tdTomato)Hze / J female mice (n = 3), 8-week-old wild-type female mice (sham group, n = 9; SCI group, n = 9), 1-week-old (sham group, n = 6; SCI group, n = 6) and 2-week-old juvenile mice (sham group, n = 6; SCI group, n = 6), were used for spinal cord crush model construction. Contusion and crush models at T10 were established as we previously reported (Zhao et al, 2022). The sham-treated mice received laminectomy without contusion and crush.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of tissue slices, immunofluorescence experiments and analysis were carried out based on our previous methods (Zhao et al, 2022). Mice were euthanized at 2 weeks post injury (2 WPI).…”
Section: Immunofluorescence Staining and Quantitative Image Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the limited regenerative capacity of neural stem cells in the central nervous system, neurons in the spinal cord are hard to regenerate after injury or necrosis 4,7 . However, studies have shown that some non-coding RNAs and transcription factors can promote the recovery of local neural circuits by regulating the local microenvironment of the spinal cord, so as to maintain part of the nerve activity and protect the paralyzed limb [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, we do not know what changes occur in the downstream peripheral nerves after spinal cord injury that increase the di culty of wound healing in the skin and soft tissue. Spinal cord neurons cannot regenerate after injury, and rely on local microenvironment regulation to restore part of the neural circuit [10][11][12] . On the contrary, peripheral nerves have good regeneration ability under normal circumstances 8,13 .…”
Section: Introductionmentioning
confidence: 99%